2007
DOI: 10.1007/s10393-007-0120-6
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Management of Tasmanian Devils in the Context of an Emerging, Extinction-threatening Disease: Devil Facial Tumor Disease

Abstract: An emerging infectious facial cancer threatens Tasmanian devils with extinction. The disease is likely to occur across the range of the devil within 5 years. This urgent time frame requires management options that can be implemented immediately: the establishment of insurance populations, in captivity, wild-living on islands, and aiming for eradication in areas that can be isolated. The long-term options of the spontaneous or assisted evolution of resistance or development of a field-deliverable vaccine are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 48 publications
1
96
0
Order By: Relevance
“…Thus, although the minimum number of cells required for cancer transmission has not been determined (most experimental CTVT transmission studies use 10 8 viable cells), it is likely that each new tumor is founded by a small number of cells, or even a single cell. Such transmission bottlenecks may provide strong selection for friability, a feature that is characteristic of both DFTD and CTVT (Brown et al, 1980;Thacher and Bradley, 1983;Jones et al, 2007). Tight transmission bottlenecks, particularly in asexual clones, also provide conditions for genetic drift and rapid fixation of neutral or deleterious alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although the minimum number of cells required for cancer transmission has not been determined (most experimental CTVT transmission studies use 10 8 viable cells), it is likely that each new tumor is founded by a small number of cells, or even a single cell. Such transmission bottlenecks may provide strong selection for friability, a feature that is characteristic of both DFTD and CTVT (Brown et al, 1980;Thacher and Bradley, 1983;Jones et al, 2007). Tight transmission bottlenecks, particularly in asexual clones, also provide conditions for genetic drift and rapid fixation of neutral or deleterious alleles.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no available vaccine, treatment or cure for DFTD, nor any evidence for resistance in the wild. Disease management options for the devil have been discussed extensively (McCallum and Jones, 2006;Jones et al, 2007;Lunney et al, 2008;McCallum, 2008). Insurance populations of captive devils or managed isolated wild-devil colonies are considered to be the most feasible option for maintaining the devil as a viable species.…”
Section: Immunology Of Dftdmentioning
confidence: 99%
“…As Tasmanian devils are also susceptible to other types of neoplastic diseases, a specific diagnostic test that can be carried out rapidly on fixed samples is required to differentiate DFTD tumors from other cancers of similar morphological appearance. 2,10,16 DFTD was initially described as a malignant neuroendocrine neoplasm. 22 Our recent studies on the Tasmanian devil transcriptome revealed that DFTD expresses a set of genes related to the myelination pathway in the peripheral nervous system (PNS).…”
mentioning
confidence: 99%
“…In wildlife, some of the more pressing examples include marine mammal morbillivirus (Osterhaus et al, 1989), increased frequency of disease outbreaks in coral reefs (Harvell et al, 2002), a chytridiomycosis pandemic in amphibians (Daszak et al, 1999;Schloegel et al, 2006) and the rapid spread of infectious facial tumors in Tasmanian devils (Jones et al, 2007b). The diversity and apparent increase in these and other diseases in wildlife have raised concerns that pathogens may pose a substantial threat to biodiversity (Wilcove et al, 1998;Daszak et al, 2000;Harvell et al, 2002).…”
Section: Introductionmentioning
confidence: 99%